Komnas Perempuan, Consolidation Role and Institutionalization Policy Violence Sexuality in the Environment College - Krisnaldo Triguswinri (Centre for Literary and Cultural Studies, 2023)
The Role of The National Commission on Violence Against Women (Komnas Perempuan) in Permendikbud No. 30 of 2021 concerning on the Prevention and Handling of Sexual Violence in the Higher Education Environment is considered very significant. Moreover, the social and intellectual works carried out by The National Commission on Violence Against Women in advocating for survivors of violence; conducting study and research for collecting data and reports; organizing public discussions, campaigns, outreach and education related to the phenomenon of violence; and the consolidation initiated by The National Commission on Violence Against Women involving the involvement of universities, civil society organizations, religious groups, and the government resulted crucial and massive results. This study used a qualitative method with The National Commission on Violence Against Women as its research object.